NORMALIZATION ANALYSIS OF BUARAN RIVER USING THE HEC-RAS APPLICATION (THE BUKIT KENCANA RESIDENTIAL AREA TO JAKARTA CIKAMPEK TOLL) - Mohammad Imamuddin (International Journal of Civil Engineering and Infrastructure, 2022)
The channel in the Buaran River area has a channel length of 5.32 km located in the Bukit Kencana Housing Area as the upstream of the Buaran River with the smallest cross-sectional width of 0.9 m and a height of 1 m and the border of the Jakarta Cikampek Toll Road as a downstream with a width of 2.2 m and a height of 3.6 m. one of the areas of the Buaran River which experienced quite severe flooding. This was due to changes or conversion of land functions which were originally water catchment areas to settlements. The large number of buildings that stand on the body of the river makes the current section of the Buaran River unable to function optimally in accommodating flood discharges, besides that there is no public awareness in protecting the environment which can be seen from the many piles of garbage in the body of the river. The purpose of this research is to find out how big the capacity of the existing Buaran cross-section is (starting from the Bukit Kencana Residential Area to the Jakarta Cikampek Toll Road) by modeling the existing cross-section using the help of the Hec-Rass application as well as recording and mapping locations that have the potential to flood. . One of the efforts that have been made by the government in controlling floods is by normalizing the river but in practice, the normalization of the Buaran River cannot be said to be running optimally. Based on hydrological calculations, the planned Q25 flood discharge is 16,307 m3/s. By using the help of the Hec-Ras application we can find out which river profiles need to be treated so that the handling of river normalization as an alternative to flood control can run optimally